2000
DOI: 10.2337/diabetes.49.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockade, but not normoglycemia or hyperinsulinemia, markedly diminishes stress-induced hyperglycemia in diabetic dogs.

Abstract: Stress-induced hyperglycemia can lead to significant deterioration in glycemic control in individuals with diabetes. Previously, we have shown in normal dogs that, after intracerebroventricular (ICV) administration of carbachol (a model of moderate stress), increases in both the metabolic clearance rate (MCR) of glucose and endogenous glucose production (GP) occur. Howe v e r, in hyperglycemic diabetic dogs subjected to the same stress, the MCR of glucose does not increase and glycemia therefore markedly deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…9A) and is due to a marked increase of glucose metabolic clearance. We made a similar observation in diabetic dogs, where stress (intracerebroventricular injection of carbachol) caused hyperglycemia in normal but not in diabetic dogs; this response was prevented by infusion of propranolol (54). The potential role of ␤-blockade in preventing hyperglycemia following stress or intense exercise remains to be explored.…”
Section: Effects Of Epi and Ne Infusion Of During Moderate Exercisementioning
confidence: 77%
“…9A) and is due to a marked increase of glucose metabolic clearance. We made a similar observation in diabetic dogs, where stress (intracerebroventricular injection of carbachol) caused hyperglycemia in normal but not in diabetic dogs; this response was prevented by infusion of propranolol (54). The potential role of ␤-blockade in preventing hyperglycemia following stress or intense exercise remains to be explored.…”
Section: Effects Of Epi and Ne Infusion Of During Moderate Exercisementioning
confidence: 77%
“…The fact that insulin treatment raised basal epinephrine levels in STZ animals suggested that low epinephrine levels in diabetes may be a direct effect of hypoinsulinemia on adrenomedullary function and/or prolonged exposure to elevated glucocorticoid levels. Unchanged insulin values during the fed and fasted state could be the cause of elevated epinephrine levels during insulin treatment (44). With phloridzin treatment, we saw epinephrine levels that were The lower basal plasma glucagon levels in insulin-treated diabetic animals may stem from suppressed glucagon release by the high plasma insulin levels resulting from the insulin implant.…”
Section: Basal Studiesmentioning
confidence: 79%
“…However, endogenous insulin production is suppressed with significant exogenous insulin administration [32,35,41]. In addition, endogenous glucose production is known to be unsuppressed by insulin or glycaemia under conditions of stress [19,20]. Hence, in this study, an unknown glucose supply is assumed and its effect is lumped in the time-varying parameter, p G while endogenous insulin production is assumed to be suppressed to a steady constant value under significant exogenous insulin input.…”
Section: System Modelmentioning
confidence: 99%
“…More specifically, high effective insulin resistance due to stress of condition and increased counter-regulatory dynamics can result in hyperglycaemia regardless of hyperinsulinaemia [17,18]. Metabolic clearance rate is not stimulated with hyperinsulinaemia under conditions of stress, as endogenous glucose production is, which compounds hyperglycaemia [19,20]. Insulin effect can also saturate at the supraphysiological insulin concentrations that exist under aggressive insulin therapy [18,[21][22][23][24][25], limiting the achievable glycaemic reduction using insulin alone if effective insulin resistance is high.…”
Section: Introductionmentioning
confidence: 99%